Theory Development and Crime Prevention Insights From the NCVS - Tseloni, Andromachi (Journal of contemporary criminal justice, 2025)
The National Crime Victimization Survey (NCVS) has furnished U.S. crime statistics and high quality data for theory development and policy insights for over 50 years. This article highlights few of these achievements drawing on the development of criminological thinking with regard to measurement, and explanation of victimization and its concentration on a small minority of the population. It overviews lifestyle and the more encompassing environmental criminology theory for victimization, and explanations of multiple victimization, and the international crime drop that relied on NCVS data. Selected crime prevention insight and few recommendations for future research conclude the article.